Optimalisasi Substitusi Tepung Azolla Terfermentasi Pada Pakan Ikan Untuk Meningkatkan Produktivitas Ikan Nila Gift - Handajani, Hany (Department Industrial Engineering, University of Muhammadiyah Malang, 2011)
The research has been conducted to evaluate the fermented azolla flour substitutions that optimize the growth rate and digestibility in Tilapia. The research was based on CompletelyRandomized Design (CRD) with three replications. Four levels of substitution of soy meal with fermented azolla flour were: P0 (100%:0%), P1 (85%:15%), P2 (70%:30%), and P3 (55%:45%). The main parameters were absolute growth rate, feed conversion, and digestibility of Tilapia (Oreochiomis sp.). The result showed that the substitution of soy meal with fermented azollaflour has significant effect into growth rate and digestibility parameters. The P1 treatment gave the best result with growth absolute rate 0,81 gram, feed conversion 3,14 and 67,68% digestibility.